2020
DOI: 10.1039/d0dt01743d
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of tetranuclear 3d–4f helicates as highly efficient catalysts for CO2 cycloaddition reactions under mild conditions

Abstract: A series of 4-nuclear lanthanide clusters supported by organic ligands Zn3LnL4 (Ln = Dy(1), Gd(2), Er(3)) were synthesized. These helicates could be used to convert CO2 into cyclic carbonates with TOF up to 38 000 h−1, without being influenced by moisture or air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…Based on the recently reported mechanism of the cycloaddition of CO 2 and epoxides, [106][107][108] we explore and propose a…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…Based on the recently reported mechanism of the cycloaddition of CO 2 and epoxides, [106][107][108] we explore and propose a…”
Section: Catalytic Propertiesmentioning
confidence: 99%
“…Recently, heterometallic polynuclear clusters employed in this catalytic reaction have attracted widespread interest and exhibited significant catalytic activities. 33,34 The research findings show that two or more metal centers lead to potential intramolecular synergistic action, which mainly results in high catalytic efficiency and selectivity under mild conditions. 35,36 Moreover, controllable structures of clusters would modulate catalytic properties with good generality and enhanced recyclability.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Domino, Friedel-Crafts, Mannich, Michael addition and cross-coupling reactions have all been successfully catalyzed by polynuclear 3d-4f coordination clusters. 14,15 Enhanced CO 2 transformations by asymmetric Zn-Ln complexes, [16][17][18][19] and catalytic olefin hydrogenation promoted by Ni-Lu complexes-in which lanthanide coordination was crucial for tuning and exploiting the reactivity at the Ni centerhave also been reported in the last five years. 20 Lanthanides incorporated into Mn-based water oxidation cluster mimics modulate the Mn potentials, as well as the O-atom transfer activities of these systems.…”
Section: Introductionmentioning
confidence: 95%
“…Catalysis involving 3d–4f complexes also is a quickly developing field; lanthanides can have a marked effect on both small molecule and organometallic reactions. Domino, Friedel–Crafts, Mannich, Michael addition, and cross-coupling reactions have all been successfully catalyzed by polynuclear 3d–4f coordination clusters. , Enhanced CO 2 transformations by asymmetric Zn–Ln complexes and catalytic olefin hydrogenation promoted by Ni–Lu complexesin which lanthanide coordination was crucial for tuning and exploiting the reactivity at the Ni centerhave also been reported in the past five years . Lanthanides incorporated into Mn-based water oxidation cluster mimics modulate the Mn potentials as well as the O-atom transfer activities of these systems. , The first examples of molecular 3d–4f water oxidation catalysts (WOCs), a Co 3 Ln (Ln = Ho–Yb) cubane series reported by Evangelisti et al, also showed enhanced photocatalytic performance compared to Co-only molecular WOCs …”
Section: Introductionmentioning
confidence: 96%